Evaluation of LSP P1 Certification Test Implementation on Competency Improvement for Vocational High School Graduates Using CIPP Model - Mustakim, Waradzi; Witari, Intan; Ambiyar, Ambiyar; Rizal, Fahmi; Verawardina, Unung (Universitas Lampung, 2023)
In the Department of Computer and Network Engineering at SMK Negeri 1 Tilatang Kamang, the LSP P1 competency certification test has been implemented to enhance student proficiency using the CIPP paradigm. A CIPP approach is used in the study method, which comprises context, input, process, product, and overall elements. The study's sample consisted of a total of two assessors. The entire population serves as the sample. A survey is the instrument utilized. approaches for data analysis that employs descriptive analysis. Using a level category method, describe the data. The outcomes demonstrated that SMK Negeri 1 Tilatang Kamang implemented the competency certification test for vocational students in the computer and network engineering expertise program in terms of the following aspects: (1) context, with a quality achievement value of 45.60 or (89.00%); (2) input, with a quality achievement value of 58.40 or (88.25%); (3) process, with a quality achievement value of 37.60 or (84.65%); (4) product, with a quality achievement value of 30.20 or (88.87%); and (5) overall, with a quality achievement value of 30.20 or (88.87%). To finish the program and ensure that graduates receive SKKNI level 2 competency certificates, competency certification examinations should be implemented gradually.